Signaling defenses with color: a meta‐analysis of leaf color variation, palatability, and herbivore damage - Cornelissen, Tatiana; Silveira, Fernando A. O.; Gomes, Susan Vieira; Lopez‐Goldar, Xosé; Martin‐Eberhardt, Sylvie; Wetzel, William (The New phytologist, 2025)
Summary We investigated the impact of leaf color variation on herbivory, testing current hypotheses indicating that leaf color could influence herbivory through bottom‐up control (by signaling leaf quality and defenses) or top‐down control (by attracting predators). A comprehensive phylogenetic meta‐analysis was conducted to assess the effects of leaf color on defense traits, leaf palatability, herbivore fitness, and herbivory. We show that nongreen leaves were better defended, less nutritive, and experienced less herbivory, leading to a reduction in herbivore fitness. Stronger effects of leaf color on herbivory were found in tropical plants, whereas lowered leaf quality in nongreen leaves was found in temperate plants. Increased leaf defense and reduction in insect fitness traits were observed in both temperate and tropical nongreen leaves. Our results indicate that leaf color plays a significant role in shaping plant defenses, leaf nutritive value, and herbivore fitness, ultimately modulating levels of herbivory. This suggests coordination between leaf color, defenses, and quality, which may be responsible for patterns of variation in herbivory and fitness‐related traits in herbivores.